Screening for the ancient polar bear mitochondrial genome reveals low integration of mitochondrial pseudogenes (numts) in bears. Issue 1 (1st January 2017) - Lammers, Fritjof; Janke, Axel; Rücklé, Cornelia; Zizka, Vera; Nilsson, Maria A.
Abstract: Phylogenetic analyses of nuclear and mitochondrial genomes indicate that polar bears captured the brown bear mitochondrial genome 160, 000 years ago, leading to an extinction of the original polar bear mitochondrial genome. However, mitochondrial DNA occasionally integrates into the nuclear genome, forming pseudogenes called numts (nuclear mitochondrial integrations). Screening the polar bear genome identified only 13 numts . Genomic analyses of two additional ursine bears and giant panda indicate that all except one of the discovered numts entered the bear lineage at least 14 million years ago. However, short read genome assemblies might lead to an under-representation of numts or other repetitive sequences. Our findings suggest low integration rates of numts in bears and a loss of the original polar bear mitochondrial genome.